EVALUATING THE IMPACT OF FODDER PURCHASE AS A DROUGHT MITIGATION STRATEGY FOR SMALLHOLDER CATTLE HOLDINGS IN SOUTH AFRICA - Nketiah, Prince; Ntuli, Herbert; Tetteh, Bright K D (Socio-Economics/Agribusiness Department, 2024)
The study set out to investigate how fodder-purchase as a drought response strategy impacts smallholder cattle farmers' (SCF) cattle inventory during drought years. Information on self-financed fodder purchasing as a drought mitigation strategy is thin in the literature. We used pooled survey data from the National Income Dynamics Study (NIDS) collated in the years 2015 and 2017 in South Africa. The nationally representative data was comprised of smallholder cattle households that experienced 2015 to 2017 sustained drought events in South Africa. Propensity score matching method (PSM) was used for the analysis. Factors that influence SCF's decision to adopt fodder purchasing as a drought mitigation strategy include age, income, market participation, crop farm ownership, recipients of secondary off-farm income, social support beneficiaries and land ownership. The PSM result shows that fodder-purchase significantly and positively impacts smallholder cattle production during drought.